2022
DOI: 10.1007/s10461-022-03805-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Automated Directly Observed Therapy for Measurement and Support of PrEP Adherence Among Young Men Who have Sex with Men

Abstract: Measurement of adherence to oral pre-exposure prophylaxis (PrEP) in real-time has been challenging. We developed DOT Diary, a smartphone application that combines automated directly observed therapy with a PrEP adherence visualization toolkit, and tested its ability to measure PrEP adherence and to increase adherence among a diverse cohort of young men who have sex with men (MSM). We enrolled 100 MSM in San Francisco and Atlanta and randomly assigned them 2:1 to DOT Diary versus standard of care. Concordance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…For example, digital pill systems have documented barriers to engagement and have not shown that they independently improve PrEP adherence compared to a standard of care. [26][27][28][29] Further, DHIs implemented to address other health problems in target youth populations have encountered problems effectively engaging participants. For example, one study which developed a mobile app for self-management of Type 1 diabetes among adolescents found no association between intervention condition and primary or secondary clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, digital pill systems have documented barriers to engagement and have not shown that they independently improve PrEP adherence compared to a standard of care. [26][27][28][29] Further, DHIs implemented to address other health problems in target youth populations have encountered problems effectively engaging participants. For example, one study which developed a mobile app for self-management of Type 1 diabetes among adolescents found no association between intervention condition and primary or secondary clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…After removing 98.23% (1163/1184) of irrelevant items, 21 studies were examined in depth. Of these 21 studies, 12 (57%) [17][18][19][20][21][22][23][24][25][26][27][28] were excluded with reasons (Textbox 3): 3 (25%) [21,23,25] were excluded as they were chatbot acceptance studies only without implementation of the chatbot project; 3 (25%) [17,18,22] were excluded as they described digital tools, which, despite being AI-enhanced, did not fully meet our inclusion criteria (not being able to dynamically interact with the client or patient); 1 (8%) [17] was a usability study that lacked the implementation part; 1 (8%) [19] was not retained as it performed a content analysis of health-related information concerning HIV pre-exposure prophylaxis (PrEP); another study (8%) [20] was excluded as it explored how text-based conversational agents express their gender and sexual identity, which was not related to our topic of interest and research aims or objectives; and 3 (25%) further studies [24,27,28] were excluded as the population also comprised non-LGBTQ individuals. Finally, an app called Rainbow Austin [26] was excluded because of lack of details.…”
Section: Search Resultsmentioning
confidence: 99%
“…Development and prior testing of PrEPmate and DOT Diary in English-speaking MSM have been described previously [ 31 , 34 - 35 ]. Briefly, PrEPmate is a text messaging–based intervention grounded in the information, motivation, behavioral skills theory of behavior change [ 36 ].…”
Section: Methodsmentioning
confidence: 99%